2020
DOI: 10.1101/2020.02.09.20021261
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of travel restrictions on the spread of the 2019 novel coronavirus (2019-nCoV) outbreak

Abstract: Motivated by the rapid spread of a novel coronavirus (2019-nCoV) in Mainland China, we use a global metapopulation disease transmission model to project the impact of both domestic and international travel limitations on the national and international spread of the epidemic. The model is calibrated on the evidence of internationally imported cases before the implementation of the travel quarantine of Wuhan. By assuming a generation time of 7.5 days, the reproduction number is estimated to be 2.4 [90% CI 2.2-2… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
186
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 235 publications
(196 citation statements)
references
References 13 publications
4
186
0
6
Order By: Relevance
“…The reduced volume of exported cases was estimated to be as large as 226 cases outside China. Our estimate is consistent with an assessment by Chinazzi et al [20], which indicated that the exported cases would be reduced by 80% by the end of February. In addition to appropriately quantifying the impact on prevention of exported cases, we have estimated the median time delay to a major epidemic assuming plausible values of R 0 at 1.5, 2.2, and 3.7.…”
Section: Discussionsupporting
confidence: 93%
“…The reduced volume of exported cases was estimated to be as large as 226 cases outside China. Our estimate is consistent with an assessment by Chinazzi et al [20], which indicated that the exported cases would be reduced by 80% by the end of February. In addition to appropriately quantifying the impact on prevention of exported cases, we have estimated the median time delay to a major epidemic assuming plausible values of R 0 at 1.5, 2.2, and 3.7.…”
Section: Discussionsupporting
confidence: 93%
“…According to [43], the average incubation period of 2019-nCoV is up to 10 days. Thus, our estimated dynamic transmission routes supports the significant effectiveness of the interventions taken by the Chinese authorities [14][15][16][17][18][19][20][21][22][23][24]. This is evidenced by On the other hand, from February 5 to 16, Table 1 suggests that the averaged magnitudes of self-transmission on each day were strengthening steadily.…”
Section: Discussionsupporting
confidence: 75%
“…On 23 January, the Chinese authorities introduced travel restrictions on five cities (Wuhan, Huanggang, Ezhou, Chibi and Zhijiang) of Hubei, shutting down the movement of more than 40 million people [14]. Among existing research, most argues that those interventions have effectively halted the spread of the 2019-nCoV [14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…As of February 20, 2020, 30 approximates the maximum known number of cases imported to any single country (World Health Organization, 2020b), and thus our analysis incorporates a reasonable degree of binomial uncertainty. The actual number of infected travellers passing through screening in any given location may be higher or lower than 30, and will depend on patterns of global connectivity, and on the duration of the source epidemic (Chinazzi et al, 2020;de Salazar et al, 2020). Finally, we analysed the sensitivity of screening effectiveness (fraction of travellers detected) to each parameter, as measured by the partial rank correlation coefficient (PRCC) (Marino et al, 2008).…”
Section: -7 Daysmentioning
confidence: 99%